ChemInform Abstract: Polyfunctional 4‐Quinolinones. Synthesis of 2‐Substituted 3‐Hydroxy‐4‐oxo‐1, 4‐dihydroquinolines. Issue 27 (16th June 2016) - Shmidt, Maria S.; Perillo, Isabel A.; Camelli, Alicia; Fernandez, Maria A.; Blanco, Maria M.
Abstract: Two new methods to obtain title compounds (II) and (V) based on rearrangement reactions are described.